Radiation−condensation instability in tokamaks with mixed impurities - Morozov, D. Kh; Pshenov, A. A. (Plasma physics reports, 2015)
Radiation−condensation instability (RCI) is one of the possible mechanisms behind the formation of microfaceted asymmetric radiation from the edge (MARFE) of a tokamak. It has been previously shown by the authors that RCI in carbon-seeded plasma can be stabilized using neon injection. Recently, beryllium- and tungsten-seeded plasmas became a subject of great interest. Therefore, in the present paper, RCI stability analysis of the edge plasma seeded with beryllium, tungsten, nitrogen, and carbon is performed. The influence of neutral hydrogen fluxes from the wall on the marginal stability limit is studied as well.